Patient Perspectives on Evolving Diverticulitis Treatment: An Assessment of Patient Willingness to Enroll in a Randomized Controlled Trial - Annie Altman-Merino, MD; Kemberlee Bonnet, MA; David Schlundt, PhD; Jesse Wrenn, MD, PhD; Wesley H. Self, MD, MPH; Elisa J. Gordon, PhD, MPH; Alexander T. Hawkins, MD, MPH (Annals of Surgery Open)
Objective:. The objective of the study was to assess patients’ attitudes regarding participation in a randomized trial of antibiotics versus placebo for acute diverticulitis. Background:. Despite evidence that antibiotics may not be necessary to treat acute uncomplicated diverticulitis, they remain the mainstay of treatment in the United States. A randomized trial in the United States evaluating antibiotic effectiveness could accelerate the implementation of antibiotic-free treatment, but providers maintain concerns that patients may be unwilling to participate. Methods:. This mixed-methods study conducted semi-structured interviews of patients presenting to a quaternary care emergency department with acute diverticulitis and a web-based survey of a larger cohort. The interviews assessed patients’ experiences with diverticulitis and perceptions of participation in a trial comparing antibiotics versus placebo. The survey quantified patients’ willingness to participate in such a study and the relative importance of factors influencing the process. Results:. Thirteen patients completed an interview. Reasons to participate included a desire to help others or contribute to scientific knowledge. Doubts about the efficacy of observation as a treatment method were the main barrier to participation. In a survey of 218 subjects, 62% of respondents reported willingness to participate in a randomized clinical trial. “What my doctor thinks,” followed by “What I have experienced in the past” were the most important decision-making factors. Conclusion:. Patients with acute uncomplicated diverticulitis maintain complex and varying perceptions of antibiotic use. Most surveyed patients would be willing to participate in a trial of antibiotics versus placebo. Our findings support the trial’s feasibility and may facilitate an informed approach to recruitment and consent.